Rethinking Consumer-Centric Markets Under Uncertainty: A Robust Approach to Community-Based Energy Trades - Onugha, Ifeoma; Dehghan, Shahab; Aristidou, Petros (My University, 2020)
The flexibility of the end users in the electricity markets is becoming more pertinent with the evolution of market mechanisms allowing consumers to participate actively. The advent of Distributed Energy Resources (DERs) and energy storage systems is gradually and continuously changing the roles of the market operators. The impact of the uncertainty of DERs and load demands on community-based market structures has not been fully investigated. In this paper, we propose a robust solution to community-based market operations under uncertainty and compare the optimal decisions on energy trades with deterministic, stochastic, and opportunistic models. Also, we employ the Taguchi’s orthogonal array testing (TOAT) to generate proficient scenarios from uncertain variables of prosumers. The proposed method is tested on a community-based microgrid with 15 prosumers assuming a single-rate tariff structure. Simulation results demonstrate the cost of robustness and the impact of uncertainty.
Keywords: Community-Based Markets; Taguchi orthogonal array testing (TOAT); Peer-to-Peer (P2P) Markets; Uncertainty